(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Significant growth of modern pharmaceutical industry implies exchange of knowledge and technology between people of different cultures. We study ways to improve international communication by theoretical and experimental methods of psycholinguistics. The paper presents a piece of experimental reconstruction of professional language consciousness of pharmaceutical specialists as native English speakers.